PPARgamma in Metabolism, Immunity, and Cancer: Unified and Diverse Mechanisms of Action - Hernandez-Quiles, Miguel; Broekema, Marjoleine F.; Kalkhoven, Eric (Frontiers in Endocrinology, 2021)
The proliferator-activated receptor γ (PPARγ), a member of the nuclear receptor superfamily, is one of the most extensively studied ligand-inducible transcription factors. Since its identification in the early 1990’s, PPARγ is best known for its critical role in adipocyte differentiation, maintenance, and function. Emerging evidence indicates that PPARγ is also important for the maturation and function of various immune system-related cell types, such as monocytes/macrophages, dendritic cells, and lymphocytes. Furthermore, PPARγ controls cell proliferation in various other tissues and organs, including colon, breast, prostate, and bladder, and dysregulated of PPARγ signaling is linked to tumour development in these organs. Recent studies have shed new light on PPARγ (dys)function in these three biological settings, showing unified and diverse mechanisms of action. Classical transactivation - where PPARγ activates genes upon binding to PPAR response elements as a heterodimer with RXRα - is important in all 3 settings, as underscored by natural loss-of-function mutations in FPLD3 and loss- and gain-of-function mutations in tumours. Transrepression-where PPARγ alters gene expression independent of DNA binding - is particularly relevant in immune cells. Interestingly, gene translocations resulting in fusion of PPARγ with other gene products, which are unique to specific carcinomas, present a third mode of action, as they potentially alter PPARγ’s target gene profile. Improved understanding of the molecular mechanism underlying PPARγ activity in the complex regulatory networks in metabolism, cancer, and inflammation may help to define novel potential therapeutic strategies for prevention and treatment of obesity, diabetes, or cancer.